(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This paper deals with a new distribution called double weighted Lomax distribution and the statistical properties of this model, such as , mode , moments are studied. As well as studying the maximum likelihood estimators of this distribution.